Development of the National Food System through Digitalization and Downstreaming to Strengthen National Food Security - Fikri, Muhammad Adymas Hikal; Novita, Yustina Dhian; Gusthomi, Moh. Imam (Indonesian Journal of Environmental Law and Sustainable Development, 2023)
Geopolitical tensions in countries have triggered uncertainty in global financial, resulting in inflationary which could to global energy and food crisis, including for Indonesia. This condition must addressed with appropriate policies , one of which is the development of a digitalization and agricultural downstream system. This article used the qualitative description method, the objective of the article is presented in comprehensive manner regarding the overview of food security in Indonesia, urgency and implementation digitalization and downstream-agriculture. In-2022, Indonesia's food security index will experience decline from the previous year. This decrease was caused mainly due to decrease in food quality and safety scores.The agricultural digitalization and downstream system allows Indonesian agriculture to be further developed so that farmers gain understanding of the required land use, but the results are satisfactory and the costs are more efficient. Agricultural digitalization interpreted as changing way things are done in aspects of agriculture, from processing to marketing.Meanwhile, downstreaming is carried out by developing agricultural activities to strengthen product processing processes, as well as developing technology in processing industry sector by strengthening the bargaining position of agricultural-based processed products. Digitalization and downstreaming can implemented through digitalization upstream and downstream from production, post-harvest, warehousing, processing, marketing and financing in the food sector through optimizing the role of MSMEs. This is realized by preparing business model digital farming through distribution smart green houseto MSMEs, distribution smart farming to food clusters, distribution of post-harvest processing machines, digitalization of product marketing with start up agriculture, to market digitalization.